Peningkatan Kemampuan Sains Sederhana Anak Usia Dini Melalui Pencampuran Warna - Sunarti Sunarti; Riskal Fitri; Nasaruddin Nasaruddin (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This Classroom Action Research (CAR) is motivated by the low basic science skills of Group B children at TK Asmaul Husnah, which is caused by the dominance of passive, memorization-oriented learning. This study aims to significantly improve early childhood basic science skills through the implementation of color-mixing activities utilizing watercolor media. The research design adopts the Kemmis and McTaggart spiral model conducted in two cycles, where each cycle encompasses the stages of planning, action, observation, and reflection. The research subjects consisted of 15 children in Group B (aged 5–6 years). Data collection techniques were carried out through triangulation, combining structured observations, child development assessment sheets, and documentation. The collected data were analyzed using comparative descriptive analysis techniques to measure the percentage of classical mastery. The results showed a highly significant increase in the children's basic science skills at each stage of the action. The children's classical mastery percentage soared sharply from the initial condition (Pre-Cycle) at 0%, increased to 40.0% (6 children mastered) at the end of Cycle I, and peaked at 93.4% (14 children mastered) at the end of Cycle II. Through a guided inquiry approach, the children were not only able to conduct experiments independently and accurately identify physical color changes, but their explanatory language skills were also stimulated in explaining the cause-and-effect relationship of the formation process of new colors. Based on these empirical findings, it is concluded that color-mixing experimental activities with watercolor media are proven to be highly effective in boosting children's basic science literacy and are recommended as an active learning model in early childhood education institutions.